PENGARUH KUALITAS PRODUTUK (MINYAK MORINGA) DAN PROMOSI TERHADAP KEPUASAN PELANGGAN PADA PERUSAHAAN SESCKO CRYELON SUKSES, DILI, TIMOR LESTE - Avelina Viana Sampaio; Tomas da Costa Alves (LPPM STIE YKPN Yogyakarta, 2025)
This study aims to understand and analyze how product quality (Traditional Moringa Oil) and promotion affect customer satisfaction at Sescko Cryelon Success. The method used in this study is a quantitative approach. Data collection was carried out through observation, questionnaires, and literature studies. The study population was 246 people, and a sample of 60 respondents was selected with an accidental sampling method. The results of this study indicate that product quality has a significant positive influence on customer satisfaction, while promotion has no effect on customer satisfaction. Furthermore, the variables of product quality and promotion simultaneously have a positive and significant influence on customer satisfaction at Sescko Cryelon Success in Dili, Timor-Leste.